THE INFLUENCE OF TEACHER CREATIVITY IN THE LEARNING PROCESS OF STUDENT LEARNING OUTCOMES IN THE EDUCATION OF ISLAMIC RELIGIOUS EDUCATION CLASS VIII SMP PGRI 01 BUMI AGUNG - Wahyu Stiawan; Mr Supean Chemo; Miftahur Rohman; Khairul Hapizin; Hirlan Hirlan (Universitas Nahdlatul Ulama Lampung, 2019)
Educational institutions should ideally prioritize all aspects of learning both cognitive, affective and psychomotor. However, educational institutions at this time the learning process undertaken by educators tends to be the achievement of curriculum material targets. Teacher creativity is needed to achieve maximum learning outcomes. The purpose of this study was to determine the effect of teacher creativity in the learning process on student learning outcomes in subjects of Islamic religious education class VIII SMP PGRI 01 Bumi Agung Academic Year 2013/2014